Kualitas Pengasuhan Anak dan Celah Kekerasan di Panti Sosial Asuhan Anak: Studi Kasus di PSAA Darul Aitam Nahdlatul Wathan, Kabupaten Lombok Timur Provinsi Nusa Tenggara Barat - Fuaida, Lisma Dyawati (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2012)
This paper presents a research ﬁ ndings about the picture of children in the “panti” (childcare institutions). The phenomenon of many children who live in the “panti” are still have complete parents who still live at home. This is a picture of the large number of childcare institutions in Indonesia, both organized by community and by religious organizations. This research aimed to explain the detail assessment of the quality of child care in the Darul Aitam Nahdlatul Wathan, Lombok, in September 2006. The research method is qualitative by using 5 (ﬁ ve) aspects of quality of service as a conceptual framework: 1) professional practice, 2) personal care, 3) stafﬁ ng, 4) sources; 5) administration. The results showed that there are so many things should be addressed based on those aspects in childcare institution. Keywords: kekerasan anak, pengasuhan, panti sosial asuhan anak, hak anak.